STRATEGI MANAJEMEN KONFLIK DAN NEGOSIASI DALAM HUBUNGAN INDUSTRIAL DI PERUSAHAAN GARMEN - Vinsensia Henny Sarumaha; Tri Maryani (Media Bina Ilmiah, 2025)
This study aims to analyze conflict management strategies and negotiation processes within industrial relations at PT Hessed Indonesia, an export-oriented garment company facing various workplace dynamics. A qualitative approach using a case study method was employed through in-depth interviews, direct observations, and document analysis. The findings reveal that common conflicts include disputes over rights, interests, and employment termination. The company implements preventive strategies through policy socialization, communication training, and dialogue forums; and curative strategies through internal conflict resolution teams and escalation procedures. Negotiations are carried out in stages through bipartite and tripartite mechanisms using a win-win solution approach. The success of these strategies is influenced by open communication, active trade union participation, and compliance with global buyer standards. Nevertheless, challenges remain, such as differences in perception between management and workers and resistance to changes in work policies. This research contributes to the development of constructive industrial relations practices in labor-intensive sectors